1988
DOI: 10.1021/np50059a006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Studies on Mexican Plants Used in Traditional Medicine, VI. Additional New 4-Phenylcoumarins from Exostema caribaeum

Abstract: Six additional 4-phenylcoumarins have been isolated from the MeOH extract of the bark of Exostema caribaeum. Their structures were determined by physical and chemical methods as 4'-5'-dihydroxy-7-methoxy-4-phenyl-5,2'-oxidocoumarin [1], 5,7,4'-trimethoxy-4-phenylcoumarin [2], 5,3'-dihydroxy-7,4'-dimethoxy-4-phenylcoumarin [3], 5-O-beta-D-galactopyranosyl-7,4'-dimethoxy-4-phenylcoumarin [6], 5-O-beta-D-glucopyranosyl-3',4'-dihydroxy-7-methoxy-4-phenylcoumarin+ ++ [7], and 5-O-(6"-acetyl)-beta-D-galactopyranosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Previous reports indicated that 5,7-dimethoxy-4-pmethoxylphenylcoumarin was produced by numerous species of plants, including Hintonia latiflora (Mata et al, 1990), Exostema caribaeum (Mata et al, 1988) and Coutarea hexandra (Delle Monache et al, 1983), but nothing is known about its activity. Our study is the first in which 5,7-dimethoxy-4-p-methoxylphenylcoumarin from culture filtrates of an endophytic Streptomyces species was isolated from the root tissue of Z. officinale.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that 5,7-dimethoxy-4-pmethoxylphenylcoumarin was produced by numerous species of plants, including Hintonia latiflora (Mata et al, 1990), Exostema caribaeum (Mata et al, 1988) and Coutarea hexandra (Delle Monache et al, 1983), but nothing is known about its activity. Our study is the first in which 5,7-dimethoxy-4-p-methoxylphenylcoumarin from culture filtrates of an endophytic Streptomyces species was isolated from the root tissue of Z. officinale.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemic and antimalarial 4-Phenylcoumarins Sanchez-Viesca (1969), Mata et al (1987Mata et al ( , 1988, Noster and Kraus (1990), Pinto et al (1997) and Slijepcevic et al (1997). Gnaphalium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Even with 2D NMR it was not possible to assign exactly the quaternary carbons C-4, C-4a, and C-8a, and the position of the phenyl ring. These positions had to be assigned by comparing the shifts with literature data (10), (11), (12). Compounds with a phenyl substituent at C-4 show 13 C-shifts of 112 ± 114 ppm for C-3 and 155 ± 156 ppm for C-4 (10), (11), (12), while a substituent at C-3 shows 13 C-shifts of 122 ppm for C-3 and 139 ppm for C-4 (13).…”
Section: Resultsmentioning
confidence: 99%